Clinoptilolyte influence on the radionuclide ¹³⁷Cs removal from the animal organism - Lonin, A.Yu. (Вопросы атомной науки и техники, 2009)
The possibility of zeolite use for the radionuclide ¹³⁷Cs removal from the animal organism under internal irradiation
is investigated. The dependence of the dynamics of ¹³⁷Cs removal from the animal organism on such factors as
clinoptilolyte introduction time and dose is established. Дослiджено можливiсть використання цеолiтiв для виведення радiонуклiдiв з органiзму тварин при
внутрiшньому опромiнюваннi. Встановлено вплив на динамiку виведення ¹³⁷Cs з органiзму тварин слiдуючих факторiв - часу введення клiноптилолiту та його дози. Исследована возможность использования цеолитов для выведения радионуклидов из организма
животных при внутренних облучениях. Установлено влияние на динамику выведения ¹³⁷Cs из организма животных следующих факторов - времени введения клиноптилолита и дозировки.